The Economic Blueprint of Prabowo and Gibran: Prospects and Challenges for Indonesia’s Development - Kurniasih, Nunung; Yudianto, Yosep (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2025)
The economic blueprint presented by Prabowo Subianto and Gibran Rakabuming Raka focuses on reshaping Indonesia’s economy through industrialization, agricultural revitalization, and technological advancements. This vision aims to reduce Indonesia’s dependency on foreign goods and services, enhance domestic production, and leverage digital innovation to create a competitive global presence. The administration’s plan includes revitalizing the agricultural sector, fostering local industries, and embracing digital transformation to boost economic productivity and innovation. While their economic policies present significant growth potential, challenges such as regional inequality, infrastructure deficits, and securing sustainable financing remain critical. This article explores the prospects of their proposed economic framework and the difficulties they may encounter in transforming Indonesia into a self-reliant, digitally advanced, and globally competitive nation. By evaluating Prabowo and Gibran’s policy vision, this study assesses the long-term viability of their strategies and their potential impact on Indonesia's economic development.